Investigating the Effect of Coffee Husk Ash as Partial Replacement of Cement in Concrete C30. - Niwainamani, Laban (Kabale University, 2023)
Concrete is a mixture of aggregates and binders. From concrete ingredients, the binder, the costliest environmental-unfriendly element is cement, which is an ecological unsociable process due to the discharge of CO; gas into the atmosphere and ecological degradation. Coffee husks have been considered as agricultural by-product; as its quantity is rising, Uganda produced 6.77 million 60 kilo bags in 2021. Each kilogram produces 0.366kg of husks. Their disposal is becoming an environmental problem as they contain phenolic compounds, their release into the environment inhibit plant root growth, lead to an increase in greenhouse gas emissions through anaerobic decomposition. Hence, this study investigated the suitability of CHA as a partial replacement for OPC in conventional concrete production. CH samples were got from Nyamukana coffee milling plant in Ntungamo district (Uganda). The CI were first burnt in open furnace at (550 - 700)"C and then to muffle furnace at 600 C for 4 hours. CHA was then ground, sieved through 45 micron sieve. Chemical composition analysed using X-ray Fluorescence method, the combined composition (Silicon diode + Aluminium oxide + Iron (III) oxide = 82.61 %> 70%) which showed pozzolanic nature of CHA. LOl was 5.27% analysed using thermogravimetric method. 100 kg of CH produced 10 kg of ash. The OPC - CHA concrete at different of replacement were investigated. For this purpose, five different concrete mixes with CHA replacing cement at 0%, 5%, 10%, 15% and 20% were prepared for 30 MPa conventional concrete with water to cement ratio of 0.5 and 420 kg/m' cement content. The initial and final setting time of OPC - CHA at 5% replacement was observed to be 79 minutes and 431 minutes respectively. The slump was 36 mm at 5% replacement. The density of OPC - CHA was observed to decrease with increasing CHA replacement, a decrease of 1.17% at 5% replacement. The specific gravity of CHA was 2.62. Compressive strength test done on the cubes at 28 days. Compressive strength for 0%, 5%. 10%. 15% and 20% replacements was 34.6 N/mm", 33.6 N/mm', 32.5 N/mm", 29.5 N/mm. and 27.7 N/mm respectively. The results of the study concluded that, up to 5% replacement of OPC by CHA achieved advanced compressive strength at all test ages that is. 3, 7, 14, and 28 days of age using compressive test machine. Recommend efficient curing at early ages as the OPC - CHA showed early strength gain and checking the chemical composition, state of CHA using advanced methods such as X-Ray Diffrnction (XRD) Analysis.